The hazchem code (Australia : Safetycare Australia, 2003)
Provides an overview of where Hazchem codes are to be found, what they mean, how they are determined and calculated, and the role they play in reducing serious consequences of chemical accidents, and improving workplace safety
Title from title screen
VCD format
Keywords: Safety measures; Hazardous substances -- Safety measures